2019
DOI: 10.1097/aci.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and complications of chronic eye rubbing in ocular allergy

Abstract: Purpose of review To review the updated literature regarding eye rubbing complications and its association with ocular allergy disorders. Recent findings Atopy and ocular allergy disorders, mainly vernal keratoconjunctivitis (VKC), are strongly associated with rubbing-related complications, most probably via itching and watery eye sensations that trigger the habit of chronic eye rubbing. Vigorous and prolonged rubbing may lead to establishment of cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 38 publications
1
66
0
Order By: Relevance
“…Chronic habitual eye rubbing is a common manifestation in AKC patients and is regarded as a risk factor for ectatic corneal disorders such as KCN (Galvis et al 2017; Hashemi et al 2019). The association between the biomechanical process of rubbing the eyes and structural changes in the cornea have been reported in many studies (Shajari et al 2016; Ben‐Eli et al 2019). In addition, several studies have shown that many inflammatory cytokines were elevated in the tears of AKC patients after rubbing eyes (Shoji et al 2007; Balasubramanian et al 2013) and also been found in the tears (Lema et al 2009; Jun et al 2011) or plasma (Sobrino et al 2017) of patients with KCN.…”
Section: Introductionmentioning
confidence: 85%
“…Chronic habitual eye rubbing is a common manifestation in AKC patients and is regarded as a risk factor for ectatic corneal disorders such as KCN (Galvis et al 2017; Hashemi et al 2019). The association between the biomechanical process of rubbing the eyes and structural changes in the cornea have been reported in many studies (Shajari et al 2016; Ben‐Eli et al 2019). In addition, several studies have shown that many inflammatory cytokines were elevated in the tears of AKC patients after rubbing eyes (Shoji et al 2007; Balasubramanian et al 2013) and also been found in the tears (Lema et al 2009; Jun et al 2011) or plasma (Sobrino et al 2017) of patients with KCN.…”
Section: Introductionmentioning
confidence: 85%
“…Treatment for advanced KC has trended away from invasive procedures such as PK and even DALK toward minimally invasive procedures such as CXL, ICRS or BL transplantation. Although keratoconus is a multifactorial disease, the pathogenesis of the disease is very much affected by genetic factors and positive family history [2,8,81]. By identifying pathogenic genes and changing the structure of cell proteins, gene therapy may be a very promising and effective treatment modality to change the course of the disease [15].…”
Section: Future Directionsmentioning
confidence: 99%
“…The onset of symptoms usually presents during adolescent and may progress until the 30s. Keratoconus is associated with eye rubbing such as in allergic conjunctivitis, floppy eyelid syndrome, obstructive sleep apnea, Down's syndrome and Leber congenital amaurosis [1,[8][9][10]. Genetic predisposition accounts for an increased risk of keratoconus in patient that has a positive family history about 15 to 67 times [11].…”
Section: Introductionmentioning
confidence: 99%
“…It coaxes to stromal lysis and corneal thinning because of the increased levels of lysosomal and proteolytic enzymes with a simultaneous reduction in the levels of protease inhibitors [12]. This vicious cycle of inflammation and stromal lysis is exacerbated by recurrent eye rubbing [13], and the stable keratoconus eventually becomes progressive which increases the risk of acute hydrops [14].…”
Section: Predisposing Factorsmentioning
confidence: 99%